Review o f the court o f appeal decision in Udo v. Robson & ORS: A Call to expanding the frontiers of fundamental rights enforcement law (2021)
This article is aimed at sensitizing the Nigerian Judges and legal practitioners alike to see need to expanding and expounding the frontiers of fundamental rights enforcement procedure law to accommodate joint application for the enforcement offundamental rights matter in our law courts. Increasing rate of human rights ’ violation is alarming, even in the democratic regime which requires broad and liberal approach in the interpretation of our laws to forestall injustice. This article concludes by proposing a way forward in form of judicial activism. This article calls on Court of Appeal to override itself in subsequent appeal(s). This article, again, calls on Supreme Court to decide on this issue.